On the permissible speeds of empty freight cars mounted on 18-100 model bogies - A. M. Brzhezovskiy; O. A. Krasnobaev; A. V. Spirov; I. E. Il’in (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
Problem of ensuring motion safety of empty freight cars is most acute in relation to cars on bogies of model 18-100, which is mainly due to operational wear of wheelsets, side frames and bolsters, as well as spring suspension elements. A potential threat to traffic safety arises when a train, composed of mostly empty and lightly loaded cars, moves along track sections that have deviations in the geometry of rail track of III and higher degrees or combinations and sequences of deviations of II degree. The article presents the main results of complex studies: mathematical modeling of the dynamic interaction of the track and empty freight cars of various types of bogie wear based on the Universal Mechanism software and field tests of cars on measuring sections of tangent, easement and circular curves with a radius of 350, 650, 800, 1000 and 2050 m on the section Belorechenskaya — Maykop of the North Caucasian railway. Dynamic qualities and motion stability of empty freight cars of various types are investigated depending on the parameters of the technical condition of the running gears and the deviations of the geometry of the rail track of II and III degrees of various types and combinations when moving in tangent and curved track sections. Authors provide tables and graphs of the dependences of indicators of dynamic qualities and motion stability of universal empty freight cars of various types on the motion speed in tangent sections of the track and circular curves of various radii and easement curves containing artificial deviations of the geometry of the rail track, most negatively affecting traffic safety. Recommendations are given for correcting the regulatory documents of the Russian Railways, which regulate the permissible speed of motion of empty freight cars, depending on the technical condition of the running gear.